Principal's Managerial Competence to Improve Teachers' Pedagogic Competence in the Implementation of Eight Graduate Profiles at Mutiara District High School - Ariyana Ariyana; Saipul Bahri; Najmuddin Najmuddin (Widyagogik, 2026)
This study aims to analyze the managerial competence of school principals—comprising technical, human, and conceptual skills—in enhancing teachers’ pedagogical competence for the implementation of the Eight Dimensions of the Pancasila Student Profile (P5) at SMAN 1 and SMAN 2 Mutiara, Pidie Regency. Employing a qualitative field research design, data were collected through interviews, observations, and documentation, then analyzed using the Miles and Huberman model with source and technique triangulation to ensure validity. The findings reveal that technical competence is manifested through collaborative lesson planning and reflective evaluation, while human competence is reflected in democratic leadership and dialogical communication that fosters a supportive school climate. Furthermore, conceptual competence allows principals to formulate contextual visions and adaptive policies aligned with student characteristics. The discussion highlights that the integration of these three competencies empowers teachers to become more professional, reflective, and creative, particularly in executing project-based learning. Ultimately, the study concludes that a principal’s ability to synthesize these managerial skills is fundamental for the effective and sustainable implementation of the Pancasila Student Profile, ensuring that teachers are adequately equipped to navigate modern educational frameworks and improve student outcomes holistically.